Faith-Based Housing in Indonesia: Shari’ah Housing, Religious Identity, and Enclave - Sunesti, Yuyun (The international journal of religion and spirituality in society, 2023)
Shari’ah-based housing has witnessed significant growth in Indonesia in recent decades. This is in part due to the rise in the religious awareness of the Muslim middle class toward religious matters. This increased religious awareness is not only in relation to worship; it can also be seen in the high demand for religious or Islamic products. This article focuses on how exclusive spaces of shari’ah housing estates are formed through specific requirements, facilities, and regulations made by both developers and buyers. Using narrative inquiry approach through in-depth interviews of shari’ah housing developers and buyers in Surakarta, the present study explores the motivations of developers and buyers in choosing shari’ah housing products and how they build and maintain their homogeneous religious communities. By applying the Enclave Society theory, this study finds that both residents and developers of shari’ah housing try to promote, protect, and enhance their Muslim lifestyles, identities, and homogeneity within the shari’ah housing communities they build and choose to live in.